Determination of fully N-methylated compound in different cabbage and beetroot varieties - Sárdi, Éva; Tordai, Enikő (Acta Biologica Szegediensis, 2005)
It is proved that antioxidants have an important role in preventing cell damage-cancer, senescence and many other alterations leading to diseases. Supplementing the first pieces of experience and observations with scientific investigations has shown that food contains several components which may strengthen the common physiological functions, enhance the natural protecting systems of the body and the elimination of reactive radicals. The pyramid illustrating the “antioxidant” nutritional recommendations is based on vegetables and fruits. It is a proven fact that consuming these vegetables can restrict the absorption of carcinogenous substances and inhibit cell mutation. Cabbage and beetroot have long been used in folk medicine due to their widely known beneficial effects on human health. We carried out investigations comparing different varieties of beetroot and cabbage grown in identical circumstances. During the comparison of the quantity of quaternary ammonium compounds in cabbage varieties we have found the highest concentration of choline, while in beetroot varieties we have measured significant amount of betaine. Our results reveal well-detectable, significant differences among the analysed varieties (of both vegetable plants) which may be used in selecting the varieties most valuable with regard to human nutrition.